Sharp estimates for inner radii of systems of nonoverlapping domains and open sets - Bakhtin, A. K. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We study extremal problems of the geometric theory of functions of a complex variable. Sharp upper estimates are obtained for the product of inner radii of disjoint domains and open sets with respect to equiradial systems of points.